Effect of integrated weed management practices on performance of dry direct seeded rice (Oryza sativa L.) - Bhurer, KP; Yadav, DN; Ladha, JK; Thapa, RB; Pandey, K (Agronomy Journal of Nepal, 2013)
Weeds are serious problem in dry direct seeded rice (DDSR). A field experiment was conducted during rainy seasons of 2010 and 2011 at research farm of the Regional Agricultural Research Station (RARS) Parwanipur, to study the effect of integrated weed management practices on the performance of dry direct seeded rice. Ten treatment combinations viz; weedy, weed free (weekly), Pendimethalin fb (followed by) Bispyribac, Pendimethalin fb two hand weeding, Stale seedbed fb Bispyribac, Stale seedbed fb Pendimethalin fb Bispyribac, Mulch 4 t/ha fb Bispyribac fb one hand weeding, Stale seedbed fb mulch 4 t/ha fb Bispyribac, Pendimethalin and Sesbania co-culture fb 2,4-D Na salt fb one hand weeding and Pendimethalin fb 2,4-D fb one hand weeding were tested in a randomized complete block design and replicated thrice. Observations were taken on weed, plant growth and yield attributes, yield, and socio-economic parameters. All weed control treatments significantly reduced the weed density and dry weight of weed resulting significant increase in yield of DSR over weedy check in both years. Weed free treatment resulted the highest yield, however, it was not economical due to high cost of cultivation. The use of Pendimethalin fb 2,4-D fb one hand weeding produced yield (5161 in 2010 and 6160 kg/ha in 2011) which were statistically at par with yield (5305 in 2010 and 6319 kg/ha in 2011) obtained under the weed free treatment. Further, the highest benefit cost ratio (CBR) 1.77 and 2.22 and net return Rs 47700 and 75084/ha during 2010 and 2011, respectively, were obtained under this treatment indicating its superiority over other treatments. The grain yield, yield attributing characters viz. panicles per m2, panicle weight, filled grain per panicle, thousand grain weight as influenced by different weed management practices revealed that higher yield resulted from weed free plot followed by Pendimethalin followed by two hand weeding and Pendimethalin followed by 2,4-D followed by one hand weeding. However, the net return per unit investment resulted highest in Pendimethalin followed by 2,4-D followed by one hand weeding. This proved that amid increasing wage rate and labor scarcity integrated weed management through Pendimethalin 30 EC (stomp) @ 1 kg a. i./ha as pre- emergence herbicide application followed by 2,4-D sodium salt 80 WP @ 0.5 kg a.i./ha followed by one hand weeding or stale seed bed followed by Pendimethalin 30 EC (stomp) @ 1 kg a. i./ha followed by Bispyribac (nominee gold) @ 25 g a. i./ha 10 % @ 200 ml/ha at 20 days of seeding resulted best alternative for manual hand weeding practices giving higher net return per unit investment. Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 53-63 DOI: http://dx.doi.org/10.3126/ajn.v3i0.9006